Platelets and von Willebrand factor in atherogenesis - Wu, Melinda D. (Blood, 2017)
The role of platelet adhesion, activation, and aggregation in acute atherothrombotic events such as myocardial infarction and stroke is well established. There is increasing evidence that platelet-endothelial interactions also contribute to early atherosclerotic plaque initiation and growth. Through these interactions, platelet-derived factors can contribute to the proinflammatory and mitogenic status of resident mural cells. Among the many putative mechanisms for platelet-endothelial interactions, increased endothelial-associated von Willebrand factor, particularly in a multimerized form, which interacts with platelet glycoproteins and integrins, is a major factor and represents a therapeutic target in early atherogenesis.